Fibrous dysplasia in a 120,000+ year old Neandertal from Krapina, Croatia. - Janet Monge; Morrie Kricun; Jakov Radovčić; Davorka Radovčić; Alan Mann; David W Frayer (PLoS ONE, 2013)
We describe the first definitive case of a fibrous dysplastic neoplasm in a Neandertal rib (120.71) from the site of Krapina in present-day Croatia. The tumor predates other evidence for these kinds of tumor by well over 100,000 years. Tumors of any sort are a rare occurrence in recent archaeological periods or in living primates, but especially in the human fossil record. Several studies have surveyed bone diseases in past human populations and living primates and fibrous dysplasias occur in a low incidence. Within the class of bone tumors of the rib, fibrous dysplasia is present in living humans at a higher frequency than other bone tumors. The bony features leading to our diagnosis are described in detail. In living humans effects of the neoplasm present a broad spectrum of symptoms, from asymptomatic to debilitating. Given the incomplete nature of this rib and the lack of associated skeletal elements, we resist commenting on the health effects the tumor had on the individual. Yet, the occurrence of this neoplasm shows that at least one Neandertal suffered a common bone tumor found in modern humans.